Importance of Tourism Education and Tourismology: the case of Portugal - Salgado, Manuel (2015)
The paper pretends to discuss about the importance of Tourism Studies in Portuguese higher education institutions and their scientific and educational nature and status, mainly to interpret about their maturity levei. The research includes secondary data from Portuguese HEI' s, demonstrating the importance of this study area, and a focus group implementation to understand their development in scientlfic, disciplinary and educational fields. The HEI' s invested slgnificantly in Tourism educatlon areas, over the past thirty years. There are diversity in educative approaches and curricular organization models in Portugal. Within this context, the debate about the actual tourism educatlon organization and the institutional background in the national perspective network seems to be essential for their sustainability. The results could help the academic community to better understand the Tourismology nature and approach and their educational and scientific implications.